Comprehensive quality assessment of municipal organic waste composts produced by different preparation methods - Tognetti, Celia (2011)
In the first part of this work, the effect of municipal organic waste (MOW) composts on plant growth was evaluated in a greenhouse trial. The treatments included soil amended with 14 different composts (prepared by shredding, adding wood shavings, cocomposting with biosolids or vermicomposting), an inorganically fertilized soil, and a control soil. All of the treatments significantly increased plant growth compared to the control, and yields of three of the amended treatments were as high as that of the inorganic fertilizer treatment. When comparing differently prepared composts to the conventional compost, it was found that cocomposting MOW with biosolids was the method which most positively influenced yields (26–41% yield increases). In the second part of this work, we evaluated the effects of the different preparation methods on compost quality, using a multivariate approach. Three main quality aspects were considered collectively in a principal component analysis: organic matter and nutrient concentrations, degradability and capacity to mineralize these nutrients, and plant growth. The model was restricted to the first and second components (PC1 and PC1) which accounted for 94% of data variance. On the resulting factorial plane, four groups were distinguished. Each of the groups was compared to the reference compost to determine quality increases or decreases. Based on this analysis, it was found that cocomposting MOW with biosolids produced the highest quality products (higher total nutrient and OM concentration, nutrient mineralization potential, and plant growth). Addition of wood shavings increased OM concentration, but reduced quality in terms of the other aspects studied. Shredding was only effective to increase product quality when it was not combined with other methods, whereas vermicomposting only increased quality when MOW was not mixed with biosolids.